Peran Guru PAI Dalam Mengembangkan Nilai-Nilai Karakter Relegius pada Siswa PGRI 1 Lumajang - herman, su (Tarbawy : Jurnal Pendidikan Islam, 2020)
This research is aimed to explore the role of Islamic education teachers in developing religious character values in students, dentifying support factors and hampering implemented programs from Islamic education teachers in developing religious character values in students of SMA PGRI 1 Lumajang. This research uses a qualitative approach, the type of research is case studies, the data collection technique used observation, interviews, and documentation. The results showed that the role of Islamic religious education teachers in developing the values of religious character in students had two roles, namely when learning had the role of a teacher, mentor, leader or class manager, driver of faith awareness, motivator in learning, learning resources, facilitator, while religious activities at school make monitoring books, make questionnaires, and give assignments about religious activities carried out by students at school and at home. Supporting factors namely family factors, the surrounding environment, school environment, facilities and infrastructure, student is to use approach using individual and counseling approaches, Islamic education learning methods. Inhibiting factors namely limited time for Islamic education learning, lack of student interest in participating of religious activities, increasingly sophisticated technology, there are students who do not fill the monitoring book, lack of individual teacher approach, there are various student attitudes and behaviors.